2019
DOI: 10.1038/s41398-019-0455-0
|View full text |Cite
|
Sign up to set email alerts
|

Cortisol administration after extinction in a fear-conditioning paradigm with traumatic film clips prevents return of fear

Abstract: Cortisol is a stress hormone and potent modulator of learning and memory processes. If administered after learning, cortisol can enhance memory consolidation. Yet it is unknown whether cortisol administration after fear extinction learning strengthens extinction memory. Extinction is a crucial mechanism underlying psychotherapy of posttraumatic stress disorder (PTSD). The present study examined whether extinction can be enhanced by administering cortisol after extinction training. In a registered, randomized, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 49 publications
(61 reference statements)
0
15
0
Order By: Relevance
“…Noradrenaline has been shown to enhance extinction learning and consolidation in animals (Abraham et al 2012) and administrations of cortisol affect human extinction learning (Merz et al 2017) and enhance extinction memory consolidation in humans (Brueckner et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Noradrenaline has been shown to enhance extinction learning and consolidation in animals (Abraham et al 2012) and administrations of cortisol affect human extinction learning (Merz et al 2017) and enhance extinction memory consolidation in humans (Brueckner et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Acute MDMA administration also causes up to a 200% increase in plasma cortisol levels (Harris et al, 2002; Parrott et al, 2014) and a significant elevation in blood oxytocin through stimulation of 5‐HT 1A receptors of hypothalamic oxytocin‐producing neurons (Hunt et al, 2011; Figure 1). As we have already mentioned, preextinction administration of cortisol diminished fear recall (Merz et al, 2018), whereas post‐training application reinforced consolidation of extinction memory (Brueckner et al, 2019). Clinical studies have also shown that heightened cortisol levels enhance the effectiveness of ET in patients with PTSD (Yehuda et al, 2015) and phobic fear (de Quervain et al, 2011; Soravia et al, 2006).…”
Section: Hallucinogenic Drugsmentioning
confidence: 78%
“…This triggers GR's translocation to the nucleus, where it acts as a transcription regulator of numerous genes, while the release of GR accessory proteins mediates glucocorticoids' nongenomic actions that rely on the activity of MAPK, PI3K, and Akt kinases (Oakley & Cidlowski, 2013; Scheschowitsch et al, 2017). Depending on the time point of their application, both oxytocin and cortisol can facilitate FE processes (Brueckner et al, 2019; Lahoud & Maroun, 2013; Merz et al, 2018; Triana‐Del Rio et al, 2019). While oxytocin mainly augments extinction learning when administered after a fear recall session (Lahoud & Maroun, 2013; Triana‐Del Rio et al, 2019), cortisol can strengthen extinction memory when it is applied both before (Merz et al, 2018) and immediately after FE training (Brueckner et al, 2019).…”
Section: Molecular Mechanisms Of Fear Extinctionmentioning
confidence: 99%
See 1 more Smart Citation
“…These cortisol effects on learning and memory processes are key to our understanding of the pathogenesis and treatment of various mental disorders, including anxiety disorders and posttraumatic stress disorder ( Bentz et al, 2010 ; de Quervain et al, 2017 ). For example, cortisol itself might comprise the potential to overcome stress-induced relapses: cortisol administered prior to extinction training is supposed to strengthen the extinction memory trace, which in turn counteracts the return of fear in healthy participants as well as patients with anxiety disorders ( Soravia et al, 2006 , 2014 ; Bentz et al, 2010 , 2013 ; Brueckner et al, 2019 ). Additionally, further strategies enhancing the recall of the extinction memory trace, for example deepened extinction or occasional reinforced extinction ( Craske et al, 2014 , 2018 ), could be applied to reduce the risk of stress-induced relapses, potentially in combination with extinction generalization.…”
Section: Discussionmentioning
confidence: 99%